Utilization and Cost Analysis of Lung Transplantation and Survival After 10 Years of Adapting the Lung Allocation Score. Issue 3 (March 2019) - Keller, Cesar A.; Gonwa, Thomas A.; White, Launia J.; Rucci, March E.; Visscher, Sue L.; Kennedy, Cassie C.; Daly, Richard C.; Naessens, James M.
Abstract : Background: Lungs are allocated in the United States using the lung allocation score (LAS). We investigated the effect of LAS trends on lung transplant-related costs, healthcare utilization, and mortality. Methods: Utilization data from Mayo Clinic (Florida and Minnesota) from 2005 to 2015 were obtained from the electronic health records (N = 465). Costs were categorized as 1-year posttransplant or transplant episode and standardized using 2015 Medicare reimbursement and cost-to-charge ratios. Regression analysis was used to assess the relationship of LAS to length of stay (LOS), mortality, and cost of transplant. Results: The mean LAS at transplant increased from 45.7 to 58.3 during the study period, whereas the 1-year survival improved from 88.1% to 92.5% ( P < 0.0001). The proportion of patients transplanted with LAS of 60 or greater increased from 16.9% to 33.3%. Posttransplant, overall, and intensive care unit LOS increased with increasing LAS. Patients with higher LAS had substantially higher transplant episode costs. An increase of LAS at transplant by 10 points increased inflation-adjusted costs by 12.0% (95% confidence interval, 9.3%–14.5%). Conclusions: The mean LAS at transplant has significantly increased over time associated with increases in LOS, resource utilization and cost. Lung allocation score has not jeopardized overall survival, but a high LAS (>60) at transplant is associated with increased mortality. Abstract : Supplemental Digital Content is available in the text.